Reforming Islamic Family Justice: Integrating Legal and Psychological Perspectives in Handling Polygamy and Divorce Cases in Indonesia - Farida Nurun Nazah; Wirda Garizahaq; Dwi Nur Fauziah Ahmad; Restia Gustiana; Hashim Balas (PT. Islamic Research Publiser, 2026)
This research examines the application of legal and psychological integration in polygamy and divorce cases at the Tigaraksa Religious Court, Indonesia. The focus of this study is to assess the extent to which the psychological considerations of the parties (wives and children) are accommodated in the case examination process and the judges' decisions. This study uses a socio-legal approach with data derived from an analysis of annotations of polygamy and divorce case rulings (2022–2024), interviews with judges and mediators, and documentation of laws and regulations. The analysis was conducted thematically to identify patterns of normative and psychological considerations. The results show that the case resolution process is still dominated by a legalistic normative approach, with the use of psychological aspects not yet institutionalized systematically. The psychological perspective is limited to the mediation stage and is not an integral part of judicial considerations in decisions. Consequently, the psychosocial welfare dimension of the family is often not a primary consideration. The novelty of this research lies in the formulation of a problem-solving, justice-based psychological law integration model in the context of the Religious Court by encouraging the application of structured psychological assessments as an instrument for judges' consideration in polygamy and divorce cases. The main contribution of this research is to provide a conceptual framework and practical recommendations for family court reform in Indonesia, particularly to improve the quality of case examination, ensure the protection of women and children, and realize substantive justice oriented towards the welfare of the family.